Structural Adaptations to Environments - Yasai‐Ardekani, Masoud (Academy of Management Review, 1986)
This paper develops a conceptual model combining ideas from organization theory and industrial economics. According to this model, objective industry environments influence managers' perceptions of their environments, and managers' perceptions influence structural adaptations. As well as industry environments, individuals' characteristics and organizational structures also influence managers' perceptions. In contrast with other models, this model examines managers' perceptions in terms of several dimensions. Managerial choice and organizational slack also influence structural adaptations to environments.